A qualitative study of older people's experience of living with neurogenic claudication to inform the development of a physiotherapy intervention. Issue 10 (8th May 2017) - Lyle, Samantha; Williamson, Esther; Darton, Frances; Griffiths, Frances; Lamb, Sarah E.
Abstract: Purpose: The aim of this study was to explore older people's experiences of living with neurogenic claudication (NC), their preferences for physiotherapy treatment provision and associated outcomes in order to inform an intervention to be tested in a clinical trial. Method: Patients with a diagnosis of NC and/or lumbar spinal stenosis were recruited through a UK NHS tertiary care center. Semi-structured interviews and self-report questionnaires were used to obtain data. A thematic analysis was conducted. Results: 15 participants were recruited; half were classed as frail older adults. Pain and the threat of pain was a prominent feature of participants' experience of NC. This led to a loss of engagement in meaningful activities and sense of self. Discourses of ageing influenced experiences as well as treatment preferences, particularly the acceptability of walking aids. A combination of one-to-one and group setting for treatment was preferred. Outcome preferences related to re-engagement in meaningful activities and pain reduction. Limitations relate to generalisability of the findings for NC patients not under physiotherapy treatment. Conclusion: We have obtained important findings about older people's experiences of living with NC and preferences for physiotherapy treatment and outcomes. These will be incorporated into an evidence-based intervention and evaluated in a randomized controlled trial. Implications for rehabilitation: Older people living with NC want to get back to meaningful activities and learn how to live with the threat of pain. Allied health professionals (AHPs) should be sensitive to the complex and ambiguous ways in which older people live with ageing and age-related decline. AHPs are in a position to support patients' successful transition to the use of walking aids thereby reducing stigmatizing effects and increasing activity. AHPs should consider a mixture of one-to-one and group classes to enable rehabilitation for older NC patients.